Analysis of the Implementation of the Principle of Good Governance: Responsiveness in Improving Public Services at the Saketi District Office, Pandeglang Regency - Ali Nurdin; Nursyifa Eriyani (Business and Investment Review, 2025)
Responsive public services are one of the important pillars in the implementation of the principles of good governance. However, in practice, the responsiveness of services at the Saketi District Office, Pandeglang Regency still faces various obstacles, especially in terms of the accuracy of response, speed of service, and the effectiveness of communication between the apparatus and the community. This study aims to analyze the implementation of good governance principles, especially the responsiveness aspect in improving the quality of public services in the Sageti District Office. The research method used is qualitative descriptive with data collection techniques through observation, interviews, and documentation. The analysis is focused on four indicators of responsiveness according to Zeithaml, namely the ability to respond to the community, speed, precision, and timeliness of services. The results of the study show that in general, the principle of good governance in the aspect of responsiveness has been applied quite well. The sub-district apparatus is considered to be able to provide relatively fast and precise services, although there are still some obstacles in communication and consistency of service time. Increasing the capacity of human resources and strengthening the service system based on community needs are the main recommendations to improve the performance of public services in Sageti District.